Data analytics interrogates robotic surgical performance using a microsurgery-specific haptic device. (2nd July 2020) - Baghdadi, Amir; Hoshyarmanesh, Hamidreza; de Lotbiniere-Bassett, Madeleine P.; Choi, Seok Keon; Lama, Sanju; Sutherland, Garnette R.
ABSTRACT: Objectives: With the increase in robot-assisted cases, recording the quantifiable dexterity of surgeons is essential for proficiency evaluations. The present study employs sensor-based kinematics and recorded surgeon experience for evaluating a new haptic device. Methods: Thirty surgeons performed a task simulating micromanipulation with neuroArmPLUS HD and two commercially available hand-controllers. The surgical performance was evaluated based on subjective measures obtained from survey and objective features derived from the sensors. Statistical analyses were performed to assess the hand-controllers and regression analysis was used to identify the key features and develop a machine learning model for surgical skill assessment. Findings: MANCOVA tests on objective features demonstrated significance (α = 0.05) for time (p = 0.02), errors (p = 0.01), distance (p = 0.03), clutch incidents (p = 0.03), and forces (p = 0.00). The majority of metrics were in favor of neuroArmPLUS HD . The surgeons found it smoother, more comfortable, less tiring, and easier to maneuver with more realistic force feedback. The ensemble machine learning model trained with 5-fold cross-validation showed an accuracy (SD) of 0.78 (0.15) in surgeon skill classification. Conclusions: This study validates the importance of incorporating a superior haptic device in telerobotic surgery for standardization of surgical education and patient care.